2019
DOI: 10.1155/2019/3732687
|View full text |Cite
|
Sign up to set email alerts
|

Costus afer: A Systematic Review of Evidence-Based Data in support of Its Medicinal Relevance

Abstract: Costus afer (C. afer) is a plant commonly known as ginger lily, spiral ginger, or bush cane. It is reportedly used in traditional medicine practice (TMP) to treat and manage many ailments including diabetes mellitus, stomach ache, arthritis, inflammation, and gout. These purported ethnomedicinal uses have triggered many research studies on the plant to amass scientific evidence. However, these research reports are scattered, and thus, this systematic review seeks to provide a comprehensive update on it coverin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
32
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 42 publications
(62 reference statements)
0
32
0
Order By: Relevance
“…Hepatotoxicity is usually characterized by increased membrane permeability and changes in enzyme levels. In a hydrocarbon-mediated liver damge, there was a substantial decrease in serum ALP and AST within normal at 400 mg/kg of aqueous leaf extract of Costus afer (ALECA) compared to rat treated with 200 mg/kg of the extract through oral gavage (Ukpabi et al 2012;Boison et al 2019). The stem extract of Costus afer was protective inalcohol-mediated liver damage in rats, suggesting a possible bene t in alcohol liver cirrhosis (Tonkiri et al 2014;Boison et al 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hepatotoxicity is usually characterized by increased membrane permeability and changes in enzyme levels. In a hydrocarbon-mediated liver damge, there was a substantial decrease in serum ALP and AST within normal at 400 mg/kg of aqueous leaf extract of Costus afer (ALECA) compared to rat treated with 200 mg/kg of the extract through oral gavage (Ukpabi et al 2012;Boison et al 2019). The stem extract of Costus afer was protective inalcohol-mediated liver damage in rats, suggesting a possible bene t in alcohol liver cirrhosis (Tonkiri et al 2014;Boison et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have also shown that aqueous leaf extract of Costus afer (ALECA) may be organoprotective(kidney and testis) in lead-mediated kidney and testis damages via antioxidant mechanisms (Tchamgoue et al 2018, Ezejiofor andOrisakwe, 2019a;Boison et al 2019). As much as various studies have reported on exposure of single heavy studies there remain insu cient information on the heavy metal mixtures which represent the real situation of these toxicants in various environmental matrices.…”
Section: Introductionmentioning
confidence: 99%
“…Hepatotoxicity is usually characterized by increased membrane permeability and changes in enzyme levels. In a hydrocarbon-mediated liver damge, there was a substantial decrease in serum ALP and AST within normal at 400 mg/kg of aqueous leaf extract of Costus afer (ALECA) compared to rat treated with 200 mg/kg of the extract through oral gavage (Ukpabi et al 2012;Boison et al 2019). The stem extract of Costus afer was protective in alcohol-mediated liver damage in rats, suggesting a possible bene t in alcohol liver cirrhosis (Tonkiri et al 2014;Boison et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have also shown that aqueous leaf extract of Costus afer (ALECA) may be organoprotective (kidney and testis) in lead-mediated kidney and testis damages via antioxidant mechanisms (Tchamgoue et al 2018, Ezejiofor andOrisakwe, 2019a;Boison et al 2019). As much as various studies have reported on exposure of single heavy metal studies, there remain insu cient information on the heavy metal mixtures which represent the real situation of these toxicants in various environmental matrices.…”
Section: Introductionmentioning
confidence: 99%
“…Costus afer is a rhizomatous herb commonly known as ginger lily or bush cane (Okugbo & Oriakhi, 2015). Almost every part of this plant is endowed with medicinal potential in diseases, and a number of research studies have gone into finding the bioactive components of this plant with pharmacological properties to be used in the design of new drugs with lesser side effects (Boison et al., 2019). The phytochemical analysis of different parts of Costus afer in different solvents shows the presence of alkaloids, phenols, saponins, tannins, triterpenes and glycosides (Akpan, Odoemena, Nwachukwu, & Danladi, 2012; Okugbo & Oriakhi, 2015).…”
Section: Introductionmentioning
confidence: 99%